HUBUNGAN ANTARA KONTROL DIRI DENGAN PROKRASTINASI AKADEMIK PADA SISWA KELAS X SMAS AL – WASLIYAH 3 MEDAN - Wardatul Hasanah Harahap; Khairina Ulfa Syaimi; Nur Asyah; Ika Sandra Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between self-control and academic procrastination among Grade X students at SMAS Al-Washliyah 3 Medan during the 2025/2026 academic year. The study employs a quantitative approach using a correlational method. The population consists of 90 students, and a purposive sampling technique was used to select a sample of 16 students. Data collection instruments consisted of questionnaires on self-control and academic procrastination, developed based on theoretical indicators and subjected to validity and reliability testing. Data analysis using the Product Moment correlation formula yielded a correlation coefficient (r) of -0.178 and a significance value (p) of 0.255 (p < 0.05). The results indicate a relationship between self-control and academic procrastination for the 2025/2026 academic year. Specifically, the findings reveal a significant negative relationship between self-control and academic procrastination; this means that higher levels of student self-control are associated with lower levels of academic procrastination. Furthermore, the coefficient of determination was found to be 3.17%, indicating that self-control contributes 3.17% to student academic procrastination, while the remaining 96.83% is influenced by factors outside the scope of this study.